Responsible tourism and sustainability: the case of Kumarakom in Kerala, India - Angelique Chettiparamb and Jithendran Kokkranikal (Journal of Policy Research in Tourism, Leisure & Events, 2012)
This paper discusses the notion of ‘responsible tourism’ and its current use within the tourism literature. We argue that the concept as used currently means everything and therefore adds nothing to the conceptual terrain of tourism trends and nomenclatures. We then introduce our own understanding of the concept arguing that while responsible tourism is linked to sustainability initiatives such as alternative tourism, ecotourism, ethical tourism, green tourism, soft tourism, pro- poor tourism, geo-tourism, integrated tourism, community-based tourism, etc it also demarcates an analytical realm of its own. We suggest that the practical use of the term in areas where it has been adopted (such as South Africa and Kerala for instance) suggests a rather restricted use. We identified this realm as the tourism sector-specific manifestation of the corporate social responsibility (CSR) agenda. Following Flyvberg's [(2006). Five misunderstandings about case-study research. Qualitative Inquiry, 12(2), 219–245] call for exemplars and paradigmatic case studies to advance knowledge in a particular domain, the responsible tourism initiative in Kumarakon, Kerala, is presented. Discussion of the case study traces the particular governance context of Kerala and the position of tourism in the state economy. The responsible tourism initiatives at the state level and local level are then described highlighting the ‘how’ of the implementation and the impact that it has produced. Generic, non-prescriptive principles that could be said to be necessary in some form for the successful translation of responsible tourism principles to practices are then identified. Such an approach is contrasted with one that places faith in the voluntary adoption of ‘responsible’ practices by the private sector on its own. It is argued that responsible tourism can make a contribution to practice provided the conceptual terrain is delineated against other forms of tourism and if research within the terrain can unpack the particular forms of challenges that are thrown up by the delineation itself.